KEANEKARAGAMAN JENIS PRIMATA DI HUTAN LINDUNG BUKIT RENTAP DAN SEKITARNYA KABUPATEN SINTANG KALIMANTAN BARAT - tian, Agus; Said, Syafruddin; anto, Eri (JURNAL HUTAN LESTARI, 2014)
Primates play an important role in protecting the forest. Rentap Hill neighborhood has been designated as Protected Forest Menhutbun through Decree No. 405 / KPTS--II 1999 Dated June 14, 1999. Rentap Protected Forest Hill has an area of ​​about 750 ha, with a total length of 9.70 km and a height limit of 50-658 m asl. This study aims to find out the type - the type of primates in Forest Hill Rentap Hedges. The method used is the transect method with the path length of 500 m, width of track: 100 m. The tools used in this study is the location map, compass, camera, meter, tally sheet, primate identification books, binoculars and GPS. The number of primates are found at least 138 individuals consisting of 3 individual species in secondary forests as much as 74 tails, while the forest around the village as much as 64 tails. Secondary forest has a diversity index that is higher by (1.007782), the forest around perkampungan (0.692658), suggesting that the high number of primate species in a habitat causes the higher the index value. Forests around the township has a greater dominance index is (0.500488) compared to secondary forests by (0.386777). Secondary forest has an index higher species richness of (1.069958) than the forest around the village of (0.553655). Similarity index between secondary forest types and forest around the village of (0.434782), this value indicates the level of similarity of constituent populations are not much different. Hunting primates in locations Protect Forest Hill Rentap, it should be done in collaboration between community protection or in the vicinity of natural resource conservation efforts in order to avoid scarcity and even extinction as klampiau primates, kukang, as well as other wildlife. Keyword: Species diversity index, dominance index, Protected Forest Hill Rentap